Bangladesh: An Umpired Democracy - Azad, Abul Kalam (Journal of Social and Development Sciences, 2012)
This paper reveals that there has been a continuous political confrontation between two archrival political forces in Bangladesh since independence in 1971. In the course of the confrontation, the country has seemingly been divided into two forces: BAL forces and anti-BAL forces. The democratic development in this country since 1991 is a by-product of this confrontation. In 1991, because of the continued mistrust between the two confronting forces, a unique system of interim government (non-party caretaker government) was produced that kept working as a catalyst of power transfer in a democratic way from one government to another till 2008 election from 1991.